2015
DOI: 10.2134/jeq2014.05.0223
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration as Affected by Long-Term Broiler Litter Application to a Udult in the Ozark Highlands

Abstract: The United States produced 8.4 billion broiler chickens () and an estimated 10.1 to 14.3 million Mg of broiler litter (BL) in 2012. Arkansas' production of 1 billion broilers in 2012 produced an estimated 1.2 to 1.7 million Mg of BL, most of which was concentrated in the Ozark Highlands region of northwest Arkansas. Increased CO release from soils associated with agricultural practices has generated concerns regarding the contribution of certain agricultural management practices to global warming. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Reporting on the results of the first 2 yr of BL application in this same long-term study, Pirani et al (2006) demonstrated that leachate-As concentrations differed among BL rates in at least one 3-mo season and that As and Se leachate loads were at least numerically elevated in response to the increasing BL application rate. Similar results were also reported by McMullen et al (2015) for the annual summary of the 8-yr data set. However, soil leachate solution would probably undergo many reactions and attenuations, even in areas of karst geology, before it was able to mix with nearby or regional surface waters.…”
Section: Leachate Water Quality Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…Reporting on the results of the first 2 yr of BL application in this same long-term study, Pirani et al (2006) demonstrated that leachate-As concentrations differed among BL rates in at least one 3-mo season and that As and Se leachate loads were at least numerically elevated in response to the increasing BL application rate. Similar results were also reported by McMullen et al (2015) for the annual summary of the 8-yr data set. However, soil leachate solution would probably undergo many reactions and attenuations, even in areas of karst geology, before it was able to mix with nearby or regional surface waters.…”
Section: Leachate Water Quality Implicationssupporting
confidence: 88%
“…Seasonal leachate DOC load averaged 3.9 kg ha −1 across BL rates with time (Table 2). Despite a large C concentration in the applied BL, DOC leaching was relatively low from the litter treatments because the C additions from the applied BL stimulated increased soil respiration (McMullen et al, 2015). Seasonal leachate loads of all other elements and compounds measured in this study averaged <0.3 kg ha −1 across BL rates with time (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Soil moisture and temperature are the most common abiotic variables affecting soil respiration (Chen et al, 2008;Hibbard et al, 2005). Previous studies have reported positive (Brown et al, 2009), negative (Ding et al, 2010;Jones et al, 2006;McMullen et al, 2015;Singh et al, 2019), and no correlation (Al-Kaisi & Yin, 2005) between CO 2 flux and soil moisture. Moisture provides access to microbial substrates (Chen et al, 2008;Harper et al, 2005;Hibbard et al, 2005), and plant root respiration may increase with water and N availability (Valentini et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moisture provides access to microbial substrates (Chen et al., 2008; Harper et al., 2005; Hibbard et al., 2005), and plant root respiration may increase with water and N availability (Valentini et al., 2000). Soil temperature accounts for a large portion of seasonal and daily CO 2 variation (Davidson et al., 1998) and has been correlated with soil CO 2 flux in a range of environmental settings (Ding et al., 2010; Epron et al., 1999; Fang & Moncrieff, 2001; Hibbard et al., 2005; McMullen et al., 2015; Ruehr et al., 2010). As agricultural soils are important contributors to the global C cycle and C storage amounts are subject to management practices (Roberson et al., 2008), other environmental factors that affect soil respiration warrant further investigation (Hibbard et al., 2005).…”
Section: Introductionmentioning
confidence: 99%